Exploring Policy Alternatives to Improve Organizational Performance - Abd. Rahman; H. Anis Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Alternative policies are a way of generating ideas, explaining them, and evaluating them in the context of efforts to address societal issues. Or a process that uses the inquiry technique and a variety of justifications to generate and apply pertinent policy data to a political decision-making process in order to address policy issues. Along with mastery of research and development methodologies, policy alternatives also call for mastery of internally or sectorally pertinent concerns. This essay makes an effort to discuss alternate policies, strategies, paradigms of methodology and practices